Dynamic Balance of Microglia and Astrocytes Involved in the Remyelinating Effect of Ginkgolide B - Yin, Jun-Jun; He, Yan; An, Jun; Miao, Qiang; Sui, Ruo-Xuan; Wang, Qing; Yu, Jie-Zhong; Xiao, Bao-Guo; Ma, Cun-Gen (Frontiers in Cellular Neuroscience, 2020)
Multiple sclerosis (MS) is an inflammatory demyelinating disorder in the central nervous system (CNS), in which remyelination failure results in persistent neurologic impairment. Ginkgolide B (GB), a major terpene lactone and active component of Ginkgo biloba, has neuroprotective effects in several models of neurological diseases. Here, our results show, by using an in vivo cuprizone (CPZ)-induced demyelinating model, administration of GB improved behavior abnormalities, promoted myelin generation, and significantly regulated the dynamic balance of microglia and astrocytes by inhibiting the expression of TLR4, NF-κB and iNOS as well as IL-1β and TNF-α, and up-regulating the expression of Arg-1 and neurotrophic factors. GB treatment also induced the generation of oligodendrocyte precursor cells (OPCs). The dynamic balance by decreasing microglia-mediated neuroinflammation and promoting astrocyte-derived neurotrophic factors should contribute to endogenous remyelination. Despite GB treatment may represent a novel strategy for promoting myelin recovery, the precise mechanism of GB targeting microglia and astrocytes remains to be further explored.